2006
DOI: 10.1002/crat.200510550
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion and structural properties of (CuAlTe2)1–x(CuAlSe2)x solid solutions

Abstract: Investigations of the thermal expansion of (CuAlTe 2 ) 1-x (CuAlSe 2 ) x solid solutions in the temperature range from 100 to 800 K have been carried out for the first time. It has been demonstrated that the thermal expansion coefficient α L grows considerably in the temperature range from 100 to 300 K, whereas the temperature dependence above 300 K is rather weak. The isotherms of composition dependence of the thermal expansion coefficient α L for 100, 293, 500 and 800 К were constructed, and it was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was found that the range of solid solution in the terminal chalcopyrite compounds at 473 K is limited to 0<z<≈0.20 for CuInS 2 α-phase and ≈0.94<z<1.0 for CuFeS 2 γ-phase. It is necessary to take into account that it is a serious problem to determine solubility in the systems formed by the two corresponding ternary compounds of these groups [17].…”
mentioning
confidence: 99%
“…It was found that the range of solid solution in the terminal chalcopyrite compounds at 473 K is limited to 0<z<≈0.20 for CuInS 2 α-phase and ≈0.94<z<1.0 for CuFeS 2 γ-phase. It is necessary to take into account that it is a serious problem to determine solubility in the systems formed by the two corresponding ternary compounds of these groups [17].…”
mentioning
confidence: 99%
“…They crystallize in these chalcopyrite structure that closely for zinc blend. Completely these materials have direct band gaps [1]. Ternary ceramic is attractive materials in promising photovoltaic and optoelectronic requests [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Their magnetic properties for Mn-substitution were also studied [7]. It is necessary to take into account that in the study of pseudobinary systems formed by two ternary compounds of this group, the determination of the defect chemistry and solubility is a serious problem [8].…”
mentioning
confidence: 99%
“…CuBiSe 2 is reported to crystallize in the cubic lattice of fcc-type with lattice constant a = 5.69 Å and a melting point of 858 K [10]. On the other hand, the crystal system of Cu 4 Bi 4 Se 9 was determined as orthorhombic with space group Pnma and lattice constants a = 32.692(7), b = 4.1198 (8), and c = 12.202(2) Å [11]. Phase relations, that were determined in the Cu-Bi-Se phase system at 573, 623, 673, 723, 823, 923, and 1023 K, revealed the existence of four ternary phase Cu 4 Bi 4 Se 9 (phase A), Cu 1,7 Bi 4,7 Se 8 , Cu 3 Bi 5 Se 9 , and Cu 3 Bi 2 Se 6 [11].…”
mentioning
confidence: 99%